2009
DOI: 10.1111/j.1365-3156.2009.02369.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for multidrug‐resistant Plasmodium falciparum isolates and analysis of pyrimethamine resistance evolution in Uige province, Angola

Abstract: Summaryobjectives To assess the extent of drug resistance in Uige through molecular genetic analysis and to test whether the dhfr triple mutant alleles present in Angola are of southeast Asian origin.methods Seventy-one samples of blood from children admitted to the Pediatric Emergency Unit of Uige Provincial Hospital in 2004 were screened for resistance mutations at pfcrt, pfmdr1, pfdhfr, pfdhps and pfATPase6.results Mutations in pfcrt (codon76), pfmdr1 (codon86), pfdhfr (codons 51, 59, 108) and pfdhps (codon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
5
21
0
Order By: Relevance
“…Malaria is endemic in most areas of the Angolan territory, with P. falciparum as the predominant infecting species (WHO 2005). The epidemiological characteristics of malaria in Angola vary from hyper-endemic (northern and north-eastern of the country) to mesoendemic stable and mesoendemic unstable (Menegon et al 2009).…”
mentioning
confidence: 99%
“…Malaria is endemic in most areas of the Angolan territory, with P. falciparum as the predominant infecting species (WHO 2005). The epidemiological characteristics of malaria in Angola vary from hyper-endemic (northern and north-eastern of the country) to mesoendemic stable and mesoendemic unstable (Menegon et al 2009).…”
mentioning
confidence: 99%
“…Also, in Southern-Iran, L263 and A623 were reported to be wild type (Zakeri et al 2012). The presence of S769N also made occasional impacts from few studies (Jambou et al 2005;Pillai et al 2012;Zakeri et al 2012) like that of the French Guiana (Legrand et al 2008) while there are reports which observed its absence in the P. falciparum isolates that were analyzed (Mugittu et al 2006;Sisowath et al 2007;Zhang et al 2008;Ferreira et al 2008;Menegon et al 2009;Wangai et al 2011;Kwansa-Bentum et al 2011;Tanabe et al 2011;Brasil et al 2012;Saha et al 2013) or even denied the association of this SNP with artemisinin resistance (Phompradit et al 2011;Cui et al 2012). Another study from Yaounde, Cameroon, where all these four mutations were tested, high prevalence of E431K was warranted and alarmed (Tahar et al 2009).…”
Section: Discussionmentioning
confidence: 89%
“…The polymorphism of the P. falciparum K13-propeller gene, from codon 427 to codon 690, was assessed using the primers: ArtinnerF (GCCTTGTTGAAAGAAGCAGAA) and ArtouterR (CGCCATTTTCTCCTCCTGTA) and with PCR conditions described by Taylor et al [6]. Analysis of Pfcrt and Pfmdr1 genes was performed as previously reported [7, 8]. Different methods were used for the analysis of fragment of Pfdhfr gene spanning codons 51–108, Pfdhps domain (719 bp) and point mutation in PfCytB gene, according to Palmieri et al [9], Menegon et al [7] and Korsinczky et al [10], respectively.…”
Section: Case Presentationmentioning
confidence: 99%
“…Analysis of Pfcrt and Pfmdr1 genes was performed as previously reported [7, 8]. Different methods were used for the analysis of fragment of Pfdhfr gene spanning codons 51–108, Pfdhps domain (719 bp) and point mutation in PfCytB gene, according to Palmieri et al [9], Menegon et al [7] and Korsinczky et al [10], respectively. All PCR products were sent to Eurofins Genomics Company (Germany) for sequencing, and sequences were compiled and analysed by Accelrys DS Gene software.…”
Section: Case Presentationmentioning
confidence: 99%